Hesperidin from Citrus seed induces human hepatocellular carcinoma HepG2 cell apoptosis via both mitochondrial and death receptor pathways - Banjerdpongchai R. (2017)
© 2015, The Author(s). Citrus seeds are full of phenolic compounds, such as flavonoids. The aims of this study were to identify the types of flavonoids in Citrus seed extracts, the cytotoxic effect, mode of cell death, and signaling pathway in human hepatic cancer HepG2 cells. The flavonoids contain anticancer, free radical scavenging, and antioxidant activities. Neohesperidin, hesperidin, and naringin, active flavanone glycosides, were identified in Citrus seed extract. The cytotoxic effect of three compounds was in a dose-dependent manner, and IC 50 levels were determined. The sensitivity of human HepG2 cells was as follows: hesperidin > naringin > neohesperidin > naringenin. Hesperidin induced HepG2 cells to undergo apoptosis in a dose-dependent manner as evidenced by the externalization of phosphatidylserine and determined by annexin V-fluorescein isothiocyanate and propidium iodide staining using flow cytometry. Hesperidin did not induce the generation of reactive oxygen species, which was determined by using 2′,7′-dichlorohydrofluorescein diacetate and flow cytometry method. The number of hesperidin-treated HepG2 cells with the loss of mitochondrial transmembrane potential increased concentration dependently, using 3,3′-dihexyloxacarbocyanine iodide employing flow cytometry. Caspase-9, -8, and -3 activities were activated and increased in hesperidin-treated HepG2 cells. Bcl-xL protein was downregulated whereas Bax, Bak, and tBid protein levels were upregulated after treatment with hesperidin in a dose-dependent manner. In conclusion, the bioflavanone from Citrus seeds, hesperidin, induced human HepG2 cell apoptosis via mitochondrial pathway and death receptor pathway. Citrus seed flavonoids are beneficial and can be developed as anticancer drug or food supplement, which still needs further in vivo investigation in animals and human beings.